Analisa Pemanfaatan Digital Marketing Dalam Meningkatkan Penjualan UMKM di Kabupaten Kampar - Rahmad Akbar; T.Yoga Winanda; Merlia Rahmayani; Dzulhijjah Yetti; Harmi Yelmi (Jurnal Sains dan Ilmu Terapan, 2022)
Digital marketing has grown very rapidly since the high use of the internet. This level of use is triggered by the presence of smartphones at very affordable prices. But the use of digital marketing is not widely realized by business people, especially SMEs in Kampar Regency. Most SMEs in this city think that digital marketing is a place for transactions to occur, this is very different from the actual meaning of digital marketing. Social media used for digital marketing is not only focused on social media that is intentionally created for SMEs, but also social media owned by employees or employees of these SMEs. So that product marketing has a wider reach, and thus product sales from SMEs in Kampar Regency also increase.